(untitled) (Neo Science Peer Reviewed Journal, 2023)
Dostoevsky is a great writer, complex and contradictory. He entered literature as a man who perfectly understands life, lies that generate spiritual and material ignorance -he exposes hypocrisy, dishonesty. In his works, he always raises and tries to solve questions about personality and its perfection. Dostoevsky’s heroes are not like anyone else. His characters say little about poverty, suffering, riots. They were attracted to other problems. The article talks about the high artistic skill and artistic and aesthetic innovation of Dostoevsky.